2002
DOI: 10.1021/om010735s
|View full text |Cite
|
Sign up to set email alerts
|

Syntheses, Structures, and Reactivity Studies of Half-Open Ruthenocenes and Their Oxodienyl Analogues

Abstract: Improved synthetic routes to Cp*Ru(Pdl) complexes (Pdl ) 2,4-dimethylpentadienyl and various oxodienyl ligands) including Cp*Ru(η 5 -2,4-Me 2 -C 4 H 3 O) (1), Cp*Ru[η 5 -2,4-(t-Bu) 2 -C 4 H 3 O] (1′), and Cp*Ru(η 5 -2,4-Me 2 -C 5 H 5 ) (1′′) have been developed, and the relative reactivities of the resulting complexes toward oxidative addition or ligand addition reactions have been examined. Thus, the oxopentadienyl complexes 1 and 1′ and the 2,4-dimethylpentadienyl complex 1′′ were found to undergo oxidative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
34
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 61 publications
(41 citation statements)
references
References 56 publications
7
34
0
Order By: Relevance
“…Geometric parameters and bond lengths for each structure (4, 5 a, and 10-12) were found to be comparable with those previously published for complexes 1, 2, and 8, respectively (Table 3). [8,14] For each compound the phenyl and Cp* rings are co-planar, with the angle formed by the ring centroids and ruthenium atom equaling 180.028 (4), 179.968 (5 a), 176.448 (10), 177.778 (11), and 179.398 (12), respectively. The Cp*-arene interplanar separation is comparable for each complex, with an average distance of 3.52 .…”
Section: Resultsmentioning
confidence: 99%
“…Geometric parameters and bond lengths for each structure (4, 5 a, and 10-12) were found to be comparable with those previously published for complexes 1, 2, and 8, respectively (Table 3). [8,14] For each compound the phenyl and Cp* rings are co-planar, with the angle formed by the ring centroids and ruthenium atom equaling 180.028 (4), 179.968 (5 a), 176.448 (10), 177.778 (11), and 179.398 (12), respectively. The Cp*-arene interplanar separation is comparable for each complex, with an average distance of 3.52 .…”
Section: Resultsmentioning
confidence: 99%
“…The corresponding chemical shift of the quaternary carbon in the Cp* ligand of complex III appears at 110.0 ppm, which clearly suggests the higher oxidation state of the ruthenium atom [6]. From 1 H NMR data, it was found that the g 3 -pentadienyl ligand in complex III displayed typical chemical shifts for uncoordinated vinylic protons (H(C5)).…”
Section: Electrolysis Of Cp*ru(g 5 -24-dimethyl-pentadienyl) (I) In mentioning
confidence: 97%
“…A comparative study of the chemical reactions of I and II has been undertaken, and there is clear evidence for the higher reactivity of the oxopentadienyl complex II towards oxidative addition, as well as in simple addition reactions [6].…”
Section: IImentioning
confidence: 99%
See 2 more Smart Citations